Role of Chemokines in Severe Asthma - Murray, L. A.; Syed, F.; Li, L.; Griswold, D. E.; Das, A. M. (Current Drug Targets, 2006)
The severe asthma phenotype is exhibited by a subset of asthma patients whose asthma symptom is poorly controlled by current therapies. Severe asthma represents a high unmet medical need and warrants research into the mechanisms driving the underlying pathophysiology. It is hypothesized that the underlying pathology associated with severe asthma is driving the symptoms experienced by these patients, which may share common features with mild to moderate asthma or may represent a unique pathological phenotype. For the purpose of this review, the pathophysiology associated with asthma in general are described and extended to incorporate severe asthma. Chemokines may contribute towards multiple features of asthma pathophysiology and this current review focuses on the biology of chemokines pertaining to asthma pathophysiology. Chemokines are important recruiters and activators of inflammatory cells and these infiltrating cells interact with resident cells, such as fibroblasts and it is through these pathways that chemokines appear to exert multiple biological actions. Clinical trials are underway with therapeutics targeting chemokine pathways for other inflammatory diseases. It is hoped that the information generated from these studies will contribute towards furthering our understanding of chemokine biology and be applied towards targeting severe asthma.
Keywords: airway remodeling